"Setting the scene in early childhood" – an MID approach for life. (30th May 2019) - Tham, J; Calache, H; Hallett, KB
Abstract: This article presents a discussion paper for both consideration and implementation of Minimal Intervention Dentistry (MID) principles by the general dental practitioner. It argues that if these concepts can be adopted in early childhood by both the community and the profession, "Teeth for Life" can become a reality for all. Oral Health promoting behaviours can be nurtured and supported from infancy and developed into everyday living practice for a lifetime thereby maintaining an optimal quality of life. MID techniques have become more refined and supported by scientific research in the recent times and should be considered an essential clinical guideline for the future disease management.